Penerapan Konsep Arsitektur Tropis pada Restoran Union Ubud, Bali - Kadek Adi Parthama (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2023)
Ubud is a hilly area dominated by jungle, rivers, and rice fields as well as residential areas. Ubud's cool tropical climate is favored by tourists. The rapid development of tourism in Bali has led to a variety of architectural styles existing in Bali, which often erode Balinese characteristics and ignore tropical climate problems. In the midst of the proliferation of various architectural styles in Bali, Ubud is still consistent in maintaining the distinctiveness of 'Ubud' by maintaining the characteristics of tropical architecture combined with Balinese architecture. This research was conducted using qualitative methods, and the strategies used were observation, documentation, and interviews. The analysis process is done with descriptive. The results obtained show that the Union Ubud restaurant building, applies a mature tropical architectural design. Successfully realizing a building with a strong character, in harmony with Balinese architecture and economically profitable. Ubud merupakan daerah perbukitan yang didominasi dengan rimba, sungai, dan persawahan serta perumahan warga. Iklim tropis Ubud yang sejuk, digemari oleh wisatawan. Perkembangan pariwisata yang pesat di Bali, menyebabkan beragam langgam arsitektur eksis di Bali, yang tidak jarang mengkikis ciri khas Bali dan abai akan permasalahan iklim tropis. Di tengah menjamurnya berbagai langgam arsitektur di Bali, Ubud masih konsisten menjaga kekhasan “Ubud’ dengan mempertahankan ciri arsitektur tropis yang dipadukan dengan arsitektur Bali. Penelitian ini dilakukan dengan metode kualitatif, dan strategi yang digunakan adalah observasi, dokumentasi, dan wawancara. Proses analisis dilakukan dengan deskriptif. Hasil yang diperoleh menunjukan bangunan restoran Union Ubud, menerapkan perancangan arsitektur tropis yang matang. Berhasil mewujudkan bangunan dengan karakter kuat, selaras dengan arsitektur Bali dan menguntungkan secara ekonomi.